The financing structure of non-listed firms - Suzan Hol; Nico van der Wijst (Statistics Norway, Research Department, 2006)
This paper presents an analysis of how Norwegian non-listed firms are financed. Using a unique database covering all limited liability firms in Norway, both the size (leverage) and composition (maturity structure) of debt are investigated. The empirical evidence provides support for the effects of taxes, asymmetric information and size suggested in the theoretical literature, and rejects the effects of agency costs and the pecking order theory.
Keywords: G32; D92; 330; financing structure; non-listed firms; debt maturity; panel data